A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial Assessing Efficacy and Safety of a Novel Low-Dose Turmeric Extract Formulation in Healthy Adults with Chronic Knee Pain - Thanawala S; Shah R; Somepalli V; Alluri KV; Desomayanandam P; Bhuvanendran A (Dove Medical Press, 2021)
Shefali Thanawala,1 Rajat Shah,1 Venkateswarlu Somepalli,2 KrishnaRaju Venkata Alluri,2 Prabakaran Desomayanandam,3 Arun Bhuvanendran3 1Inventia Healthcare Ltd., Mumbai, Maharashtra, India; 2Laila Nutraceuticals, Vijayawada, Andhra Pradesh, India; 3In vitro Research Solutions (iVRS) Pvt Ltd, Bengaluru, Karnataka, IndiaCorrespondence: Shefali ThanawalaInventia Healthcare Ltd., Mumbai, Maharashtra, IndiaTel +91 9324210054Email shefali.thanawala@inventiahealthcare.comBackground: Knee pain causes functional limitations, eventually compromising the quality of life. We evaluated the efficacy of our water-dispersible turmeric formulation (60% natural curcuminoids, TurmXTRA 60N®—WDTE60N), which exhibited better PK profile at low dose (250 mg) than standard turmeric extract, in alleviating symptoms of chronic knee pain.Methods: In this randomized, double-blind, placebo-controlled trial, subjects received either 250 mg WDTE60N capsule (150 mg curcuminoids; n = 53) or appearance-matched placebo capsule (n = 53) once daily for 90 days. Primary endpoint was change in pain score on the visual analogue scale (VAS) after 80-m fast-paced walk test.Results: A total of 96 subjects completed the study. WDTE60N reduced VAS score from baseline (5.4 ± 0.9) to day 90 (3.8 ± 0.8) with greater mean reduction than placebo (− 1.5 ± 0.7 vs − 0.6 ± 0.8, p < 0.0001; 2.5 times). It also significantly improved the time taken for 80-m fast-paced walk test and 9-step stair-climb test; and improved all biomarkers compared to placebo (p > 0.05). Three adverse events occurred but were unrelated to study products.Conclusion: WDTE60N 250 mg administered once daily for 3 months, alleviated knee pain, improved joint function in healthy subjects with chronic knee pain, was well tolerated and safe.Keywords: biomarkers, chronic pain, curcuminoids, knee joint, turmeric, visual analog scale